Life and Water on Karst Monitoring of transboundary water resources of Northern Istria - Zupan Hajna, Nadja; Petrič, Metka; Ravbar, Nataša; Rubinić, Josip (ZRC SAZU, Založba ZRC, 2017)
The book is the result of joint work and many years of mutual cooperation between researchers from Slovenia and Croatia. It was made as part of the transboundary project ŽIVO! Življenje - voda! (Life - Water!) (IPA CBC SI-HR 2007-2013), which involved the participation of authors from project partner institutions as well as invited authors who are familiar with the characteristics of the karst area of Northern Istria and the conditions there relating to drinking water supply. The monograph presents the natural features of Northern Istria, the karst and karst phenomena, karst hydrogeology, ecology and microbiology, and highlights in particular the vulnerability of the karst to various human activities. The main focus of attention is on karst water sources. In assessing their characteristics we used available knowledge of karst water on both sides of the border and supplemented it with new research on the transboundary area in question, which was based on field measurements and sampling, and chemical, microbiological and biological analysis of water. The collected findings form the basis for planning more effective monitoring of the quality of karst water sources, their protection and consequently the improvement of their quality.First editon was published in 2015, this corrected second edition is available also in paperback (ISBN 978-961-05-0001-8).